2019
DOI: 10.21203/rs.2.19347/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Specific enrichment of microbes and increased ruminal propionate production: the potential mechanism underlying the high energy efficiency of Holstein heifers fed steam-flaked corn

Abstract: Corn grain is high in starch content and is primarily used as an energy source in ruminant diets. Compared with finely ground corn (FGC), steam-flaked corn (SFC) processing could improve the milk yield of lactating dairy cows and the growth performance of feedlot cattle, but the detailed mechanisms underlying this finding are unknown. The rumen microbiome contributes to feed efficiency by breaking down feedstuffs into energy substrates that can subsequently be utilized by the host animal. Therefore, the curren… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…These findings may explain the lower propionate concentration, as members of the Succinivibrio and Bacteroidales are known starch degraders in the rumen and found in high abundance when cattle are fed high-grain diets containing large amounts of starch or rapidly fermentable carbohydrates ( Zhang et al, 2018 ). Ren et al (2019) also reported that the relative abundance of amylolytic Succinivibrio increased as the availability of starch in the diet increased, resulting in a positive correlation with propionate concentration in the rumen, which is in agreement with the results observed in this study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings may explain the lower propionate concentration, as members of the Succinivibrio and Bacteroidales are known starch degraders in the rumen and found in high abundance when cattle are fed high-grain diets containing large amounts of starch or rapidly fermentable carbohydrates ( Zhang et al, 2018 ). Ren et al (2019) also reported that the relative abundance of amylolytic Succinivibrio increased as the availability of starch in the diet increased, resulting in a positive correlation with propionate concentration in the rumen, which is in agreement with the results observed in this study.…”
Section: Resultssupporting
confidence: 92%
“…This can present problems, such as the aforementioned ruminal acidosis, during the finishing period and negatively impact animal health and productivity. For example, the inclusion of small amounts of grain (10 to 20%) in the pre-adaptation diet prior to feedlot arrival may trigger ruminal acidosis by ensuring that adequate numbers of amylolytic microorganisms, such as those from the genus Succinivibrio , are present to ferment the carbohydrates in the adaptation and finishing diet ( Nagaraja and Titgemeyer, 2007 ; Nagaraja, 2016 ; Ren et al, 2019 ). Cattle that are nutritionally restricted to grazing on poor-quality tropical grasses prior to intake of a high-concentrate diet may respond negatively to the rapid influx of concentrate present in the adaptation diet and develop ruminal acidosis.…”
Section: Introductionmentioning
confidence: 99%
“…The different breed and feeding management can be attributed to the inconsistency of the domain genus. The Ruminococcaceae family is related to cellulose and hemicellulose degradation [ 56 ]. Diets with PM silage changed the carbohydrate resource and the fiber decomposition process may contribute to the difference between the Ruminococcaceae UCG-013 genus and other Ruminococcaceae genera [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Ruminococcaceae family is related to cellulose and hemicellulose degradation [ 56 ]. Diets with PM silage changed the carbohydrate resource and the fiber decomposition process may contribute to the difference between the Ruminococcaceae UCG-013 genus and other Ruminococcaceae genera [ 56 ]. Previous studies have indicated that the large intestine of cattle contains a small quantity of fiber and starch [ 57 ], and that the large intestine is an important organ for digesting undigested feed, suggesting that PM silage supplementation can have a positive influence on fiber degradation in the upper gut and consequently decrease the cellulolytic bacteria of the hindgut.…”
Section: Discussionmentioning
confidence: 99%
“…Succinivibrionacae are reported to be core taxa in beef cattle and one of the most active bacteria during growing and finishing stages [8,33]. Members of this family, including Selenomonas, and Succinivibrio, have been observed to increase in the rumen of steers when suppressing methanogens using encapsulated nitrates, and in positive association with high energy diets, ADG and feed efficiency [34][35][36][37].…”
Section: The Rumen Microbiome Is Unique Under Specific Bkg Systems and Finishing In Beef Cattlementioning
confidence: 99%